2010
DOI: 10.1159/000320349
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia Psychopathology in a Kuwaiti Arab Sample

Abstract: Background: The heterogeneity of schizophrenia psychopathology has led to a search for symptom clusters that could be related to broad features of the disease. The objectives of the study were to: (1) highlight the pattern of symptoms among Kuwaiti subjects with schizophrenia, using the ICD-10 symptom checklist; (2) assess the factor structure of the Brief Psychiatric Rating Scale 18 (BPRS-18) and BPRS-24, and (3) evaluate the relationship of the resulting factors with sociodemographic characteristics, age at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 117 publications
(97 reference statements)
1
12
0
Order By: Relevance
“…In another study [25], MA users reported high levels of psychiatric symptoms, including poor anger control and violent behaviors. Previous studies exploring positive symptoms in patients with schizophrenia suggested that persecutory delusions, delusional perceptions and auditory hallucinations were the most commonly observed symptoms [4,5]. The profiles of positive symptoms among MAP and schizophrenia in our study were generally compatible with previous reports.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In another study [25], MA users reported high levels of psychiatric symptoms, including poor anger control and violent behaviors. Previous studies exploring positive symptoms in patients with schizophrenia suggested that persecutory delusions, delusional perceptions and auditory hallucinations were the most commonly observed symptoms [4,5]. The profiles of positive symptoms among MAP and schizophrenia in our study were generally compatible with previous reports.…”
Section: Discussionsupporting
confidence: 91%
“…The negative symptoms indicate the absence of certain functions that are present in healthy individuals, such as anhedonia, avolition, blunted affect (BA), and poverty of speech [3]. Most patients with schizophrenia exhibit a mixture of positive and negative symptoms, which vary in degree over time [4,5]. The severity of psychotic symptoms is associated with the social functioning of patients and the burden of caregivers [6].…”
Section: Introductionmentioning
confidence: 99%
“…Only the IEQ - EU will be described in detail here because it is the focus of this report. Details about the other questionnaires have been presented elsewhere [14,42]. …”
Section: Methodsmentioning
confidence: 99%
“…), pharmacotherapy, insight, depression, pain (Pinikahana et al . ), duration of untreated illness, and severity of psychopathology (Zahid & Ohaeri ).…”
Section: Introductionmentioning
confidence: 99%